Pandemics and tourism in Acapulco during the first two decades of the XXI century - Vicente, Miguel Angel Cruz; Cedillo, José Luis Montesillo (Seven Editora, 2023)
In Acapulco tourism is the most important economic activity, it is a beach destination and main actor in the contemporary tourist history of Mexico. From its tourist beginnings it caused admiration to own (national tourism) and strangers (international tourism) for its climate and golden beaches, known as the Pearl of the Pacific; annually receives around nine million visitors, however, during the Covid-19 pandemic Acapulco "closed" its beaches to tourism and this produced a decrease in the arrival of visitors, of this fact there was no precedent, although this pandemic (by Covid-19) was not the first that occurred so far this century, the previous ones, Severe Acute Respiratory Syndrome (SARS) and A(H1N1), did not have great repercussions on tourism. The objective of this article was to carry out an analysis of the tourism results of Acapulco during the pandemics that have occurred in the first two decades of the XXI century [A(H1N1) and Covid-19]. To this end, the descriptive statistical method of the variables referring to the arrival of tourists, hotel occupancy and economic spillover during the holiday seasons that were affected during the period of duration of the pandemics before becoming endemic was used. It is concluded that there is no parallel between the pandemics of influenza A (H1N1) and Covid-19, although an analysis of the behavior of specific topics can be made. DOI:https://doi.org/10.56238/emerrelcovid19-070